HUBUNGAN KARAKTERISTIK RESPONDEN DAN SANITASI PERUMAHAN NELAYAN DENGAN KASUS TB PARU DI KELURAHAN PASAR BELAKANG KECAMATAN SIBOLGA KOTA KOTA SIBOLGA TAHUN 2012-2014 - Imerlyn A Silitonga; devi nuraini santi; taufik ashar (Lingkungan dan Kesehatan Kerja, 2014)
Pulmonary tuberculosis is a communicable disease which is caused by Mycobacterium tuberculosis which can live up to several hours in the dark and damp, but will die when exposed to ultraviolet light. Home environment with poor sanitation is one of media that gives high influence to the mycobacterium tuberculosis’s growth. The purpose of this study is to analyze the correlation between characteristics of respondents and fisherman house sanitation to Pulmonary tuberculosis Case. This is a case control research. The samples of this research was 60 respondents which is consist of 30 respondents for case that as the sufferer of pulmonary tuberculosis which recorded on the medical record of public health centre Sambas  Sibolga, and 30 respondents for Control, that was the people who lives around the sufferer of pulmonary tuberculosis in Kelurahan Pasar Belakang by matching the characteristics age and gender with case taken with purposive. The data was analiyzed by Chi Square with confidence interval was 95%. Based on the results, the characteristics of respondents variables incorrelate with pulmonary TB cases. The sanitation variables that correlate with pulmonary TB cases is residential density (p<0,05) and OR=5,714 and floor (p<0,05) and OR=3,286. Respondent’s family behaviours like hanging wet clothes indoor does have a significant correlation with pulmonary TB cases in Kelurahan Pasar Belakang (p<0,05) and OR=11. Therefore, it is required the public participation and the active role of the government and health officer’s assignment to increase the services and knowledges to prevent pulmonary tuberculosis disease by prevention through counseling, case finding and community empowerment.